2020
DOI: 10.1186/s13256-020-02469-8
|View full text |Cite
|
Sign up to set email alerts
|

Fulminant septic shock due to Edwardsiella tarda infection associated with multiple liver abscesses: a case report and review of the literature

Abstract: Introduction Edwardsiella tarda uncommonly infects humans. The usual presentation is mild gastroenteritis, but systemic manifestations may occur. Lethal infections are rarely documented in patients with underlying disorders. Case presentation A previously healthy 37-year-old Southeast Asian woman presented to our hospital with recent onset of abdominal pain, fever, and vomiting. Her condition rapidly deteriorated with signs and symptoms of fulminant septic shock; thus, she was intubated, supported with intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…Edwardsiella species are generally found in marine animals and their habitats, but humans may be incidentally infected through exposure to water environments or ingestion of contaminated raw seafood 1 . Although the gastrointestinal tract is the site most often involved (presenting as a self-limited gastroenteritis), other manifestations such as pelvic or intra-abdominal abscesses, vertebral osteomyelitis and epidural abscess, wound infections and myonecrosis, and bacteremia can occur 2–8 . Systemic infection usually presents in patients with underlying chronic conditions, and mortality rates in these patients can be as high as 50% 9–11 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Edwardsiella species are generally found in marine animals and their habitats, but humans may be incidentally infected through exposure to water environments or ingestion of contaminated raw seafood 1 . Although the gastrointestinal tract is the site most often involved (presenting as a self-limited gastroenteritis), other manifestations such as pelvic or intra-abdominal abscesses, vertebral osteomyelitis and epidural abscess, wound infections and myonecrosis, and bacteremia can occur 2–8 . Systemic infection usually presents in patients with underlying chronic conditions, and mortality rates in these patients can be as high as 50% 9–11 .…”
Section: Discussionmentioning
confidence: 99%
“…1 Although the gastrointestinal tract is the site most often involved (presenting as a self-limited gastroenteritis), other manifestations such as pelvic or intra-abdominal abscesses, vertebral osteomyelitis and epidural abscess, wound infections and myonecrosis, and bacteremia can occur. [2][3][4][5][6][7][8] Systemic infection usually presents in patients with underlying chronic conditions, and mortality rates in these patients can be as high as 50%. [9][10][11] Predisposing illnesses include diabetes, hepatobiliary and bowel diseases, sickle cell disease, and immunodeficiencies.…”
Section: Discussionmentioning
confidence: 99%
“…The most serious presentation is a systemic manifestation complex that can include septic shock, osteomyelitis, cholecystitis, and meningitis. Systemic manifestations carry a high risk of mortality [ 12 ]. Cirrhosis of the liver, immunocompromised state, and liver disease with iron overload have been the only risk factors reported for severe sepsis with E. tarda in humans.…”
Section: Discussionmentioning
confidence: 99%
“…E. tarda is a Gram-negative, facultative, anaerobic bacterium belonging to the Enterobacteriaceae family. Although E. tarda is an unusual human pathogen that mostly causes mild GI diseases in humans, it can occasionally cause invasive infections, such as abscesses, in extraintestinal organs, including the liver, biliary duct, pelvis, brain, and digestive tract (10)(11)(12)(13)(14). Some previous reports have shown that E. tarda induces gastroenteritis associated with ulceration and pseudomembranes (15)(16)(17).…”
Section: E Tarda Infection In Inflammatory Bowel Disease Patientsmentioning
confidence: 99%